Preclinical evidence of reno-protective effect of quercetin on acute kidney injury: a meta-analysis of animal studies - Zeng, Yi-Fan; Li, Jing-Yu; Wei, Xin-Yu; Ma, Si-Qing; Wang, Qiu-Guo; Qi, Zhen; Duan, Zhi-Cheng; Tan, Ling; Tang, Hao (Frontiers in Pharmacology, 2023)
Objective: This study evaluated the reno-protective effects of quercetin in animal models of acute kidney injury (AKI).We conducted a systematic search of literature published to date in PubMed, Web of Science, and EMBASE databases. Methodological quality was assessed by SYRCLE's RoB tool.Funnel plot, Egger's test, and Begg's test were used to determine publication bias.Results: A total of 19 studies with 288 animals were included in this meta-analysis. The methodology quality scores of the included studies ranged from 4 to 7. The results indicated that quercetin reduced blood urea nitrogen (SMD = -4.78; 95% CI: -6.45, -3.12; P < 0.01; I 2 = 84%) and serum creatinine (SMD: -2.73, 95% CI: -3.66, -1.80; P < 0.01; I 2 = 80%) in AKI models. The result of sensitivity analysis was stable, while the results of funnel plot indicated asymmetric. In addition, we further analyzed inflammatory cytokines, oxidative stress levels, and kidney injury scores, and found that quercetin treatment had antioxidant and anti-inflammatory effects and improved kidney injury scores in animal models of AKI.Conclusions: Quercetin exhibited a promising reno-protective effect in AKI animal models.